Possession of HLA class II DRB1*1303 associates with reduced viral loads in chronic HIV-1 clade C and B infection. - Julg, B; Moodley, E; Qi, Y; Ramduth, D; Reddy, S; Mncube, Z; Gao, X; Goulder, P; Detels, R; Ndung'u, T; Walker, B; Carrington, M (2011)
BACKGROUND: The HLA class II molecules play a central role in the generation of human immunodeficiency virus (HIV)-specific CD4(+) T-helper cells, which are critical for the induction of cytotoxic CD8(+) T cell responses. However, little is known about the impact of HLA class II alleles on HIV disease progression. METHODS: In this study we investigated the effect of HLA class II alleles on HIV disease outcome and HIV-specific T cell responses in a cohort of 426 antiretroviral therapy-naive, HIV-1 clade C-infected, predominantly female black South Africans. RESULTS: The HLA class II allele DRB1*1303 was independently associated with lower plasma viral loads in this population (P = .02), an association that was confirmed in a second cohort of 1436 untreated, HIV-1 clade B-infected, male European Americans, suggesting that DRB1*1303-mediated protection is independent of ethnicity, sex, and viral clade. Interestingly, DRB1*1303 carriage was not associated with an increased frequency of interferon (IFN) γ-positive HIV-specific CD4(+) T cell responses. CONCLUSIONS: These data demonstrate the independent effect of an HLA class II allele, DRB1*1303, on HIV disease progression, in the absence of increased IFN-γ-positive HIV-specific CD4(+) T cell frequencies, suggesting that the protective activity of DRB1*1303 may be mediated via an alternative mechanism.